Novel photocatalytic coating for corrosion mitigation in 304LSS of dry storage canisters - Sathasivam, Kamalasekaran; Wang, Mei-Ya; Anbalagan, Aswin kumar; Lee, Chih-Hao; Yeh, Tsung-Kuang (Frontiers in Materials, 2023)
Type 304L stainless steel (304LSS) is one of the candidate canister materials for storing radioactive spent fuels, usually near seashore environments along with nuclear power plants. During the prolonged exposure of dry storage canisters to saline environments, they are highly susceptible to chloride induced stress corrosion cracking. Failure of a dry storage canister not only would release radioactive isotopes into the environment, but would also lead to a costly replacement of the cracked canister. The objective of this study is to develop a multilayered titanium dioxide (TiO2) composite coating on a 304LSS substrate. With ultraviolet (UV) illumination, this coating would act as a barrier and simultaneously offer cathodic protection against corrosion in the substrate alloy. The composite coating consists of a plain amorphous TiO2 coating over another cerium-doped (Ce-doped) TiO2 coating. Electronic currents generated by photo-catalytic reaction of the amorphous TiO2 coating under UV illumination were measured. Photo-electrochemical analyses and surface morphology observations were conducted to evaluate the performance of the Ce-doped coatings on corrosion mitigation. Optimal amounts of cerium doping that offered better photo-cathodic protection were also explored. Results indicated that the Ce-doped TiO2 coating exhibited a better performance on photo-cathodic protection for 304LSS in aerated 3.5% NaCl solutions than the one without cerium doping. The underlying Ce-doped TiO2 coating was effectively charged during UV illumination, and it was able to continuously release electrons even after the UV was switched off, thus providing uninterrupted photo-cathodic protection for the coated 304LSS substrate. Keywords: Dry storage canister, 304L stainless steel (304LSS), Titanium dioxide (TiO2), cerium doping, photo-cathodic protection